Honesty based democratic scheme to improve community cooperation for Internet of Things based vehicular delay tolerant networks. Issue 1 (4th December 2020) - Rehman, Ghani ur; Ghani, Anwar; Zubair, Muhammad; Ghayyure, Shahbaz A. K.; Muhammad, Shad
Abstract: Many Internet of Things (IoT) applications have been developed and implemented on unreliable wireless networks like the delay tolerant network (DTN); however, efficient data transfer in DTN is still an important issue for the IoT applications. One of the application areas of DTN is vehicular delay tolerant network (VDTN) where the network faces communication disruption due to lack of end‐to‐end relay route. It is challenging as some of the nodes show selfish behavior to preserve their resources like memory and energy and become noncooperative. In this article, an honesty‐based democratic scheme (HBDS) is introduced where vehicles with higher honesty level are elected as heads—during the process. Vehicles involved in the process would maximize their rewards (reputation) through active participation in the network activities, whereas vehicles with noncooperative selfish behavior are punished. The honesty level of the heads is analyzed using Vickrey, Clarke, and Groves (VCG) model. The mathematical model and algorithms developed in the proposed HBDS technique are simulated using the VDTNSim framework to evaluate their efficiency. The performance results show that the proposed scheme dominates current schemes in terms of packet delivery probability, packet delivery delay, number of packets drop, and overhead ratio. Abstract : In this article, an honesty‐based democratic scheme (HBDS) is introduced where vehicles with higher honesty level are elected as heads—during the process. Vehicles involved in the process would maximize their rewards (reputation) through active participation in the network activities, whereas vehicles with noncooperative selfish behavior are punished.